Analysis of sex chromosome abnormalities using X and Y chromosome DNA tiling path arrays. Issue 7 (27th February 2007) - Karcanias, A C; Ichimura, K; Mitchell, M J; Sargent, C A; Affara, N A
Abstract : Background: Array comparative genomic hybridisation is a powerful tool for the detection of copy number changes in the genome. Methods: A human X and Y chromosome tiling path array was developed for the analysis of sex chromosome aberrations. Results: Normal X and Y chromosome profiles were established by analysis with DNA from normal fertile males and females. Detection of infertile males with known Y deletions confirmed the competence of the array to detect AZFa, AZFb and AZFc deletions and to distinguish between different AZFc lesions. Examples of terminal and interstitial deletions of Xp (previously characterised through cytogenetic and microsatellite analysis) have been assessed using the arrays, thus both confirming and refining the established deletion breakpoints. Breakpoints in iso-Yq, iso-Yp and X–Y translocation chromosomes and X–Y interchanges in XX males are also amenable to analysis. Discussion: The resolution of the tiling path clone set used allows breakpoints to be placed within 100–200 kb, permitting more precise genotype/phenotype correlations. These data indicate that the combined X and Y tiling path arrays provide an effective tool for the investigation and diagnosis of sex chromosome copy number aberrations and rearrangements.